Effect of Diet and Crude Dietary Protein Content on Reproductive Performance of The Snail Achatina Fulica (Bowdich, 1720) - Sika, Nygblé A.; Amani, N’dri S. C.; N’dri, Kouassi J. (European Journal of Applied Sciences, 2023)
The effect of diet and protein content on reproductive parameters was studied of 225 juveniles of Achatina fulica. For this, these snails were subjected to two green fodders (R1 and R2) and three concentrated flours diets (R3, R4 and R5) with different protein contents (10.5%; 14% and 17.5%), for two years in the experimental farm of Nangui Abrougoua University. The R1 diet includes Lactuca sativa (Asteraceae), Carica papaya (Caricaceae), Brassica oleracea (Brassicaceae), Cecropia peltata (Moraceae), Laportea aestuans (Urticaceae), and Phaulopsis falcisepala (Acanthaceae). The R2 diet, in addition to the leaves used for the R1 diet, is supplemented with leaves of Leucena leucocephala (Fabaceae-Mimosoideae), a relatively protein-rich plant. The animals submitted to the diets consisting of green fodder began to lay from the seventh month, whereas with the concentrated diets (R3, R4 and R5) the snails laid eggs from three months, i.e. with a reduction in the age of first lay by four months. Concentrated diets provide higher average monthly laying numbers (between 0.41 and 0.57) as well as a higher number of eggs per laying (between 215 and 233 eggs) compared to R1 and R2. The highest protein R5 diet is the one that provides the best reproductive performance. Additionally, the strong positive correlation (r=0.99) between diet protein content and laying and egg number per laying indicates that the protein content of the diet significantly improves the reproductive performance of A. fulica.